Body Structure Of Badminton Athletes Of Makassar City Tarunas Reviewed From Playing Skills - Sayuti, Herman; Kasmad, Muhammad Rachmat; Suwardi, Suwardi (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aimed to determine the body structure of badminton athletes in Makassar City in terms of playing skills. This study is correlational, intending to determine the effect of body structure on the playing skills of badminton athletes in Makassar City. The study developed in this study was conducted with a simple field study. The population in this study were all badminton athletes (aged 17-19 years) in Makassar City, totalling 73 people. The sample used in this study was badminton athletes at the cadet level throughout Makassar City using random sampling. The sample used in this study was representative of 8 PBSI clubs in Makassar City from 50 athletes who had good skills. So the total number of samples was 50 athletes from clubs in Makassar City. The test instrument is used to measure body structure (height, arm length, leg length, chest circumference, weight) and badminton playing skills (serve, smash and drop shot). The study used a descriptive analysis design by clarifying the values achieved by each athlete in the test. Then the values are added up and categorized based on the range of values (scores). The results of the study show that: (1) The body structure of the height aspect of the badminton athletes of Makassar City Cadets reviewed from the service, smash and drop shoot in badminton games is in the low category. (2) The body structure of the arm length aspect of the badminton athletes of Makassar City Cadets reviewed from the service, smash and drop shoot in badminton games is in the medium category, (3) The body structure of the chest circumference aspect of the badminton athletes of Makassar City Cadets reviewed from the service, smash and drop shoot in badminton games is in the medium category. (4) The body structure of the leg length aspect of the badminton athletes of Makassar City Cadets reviewed from the service, smash and drop shoot in badminton games is in the high category, and (5) The body structure of the weight aspect of the badminton athletes of Makassar City Cadets reviewed from the service, smash and drop shoot in badminton games is in the medium category.